Compensatory Changes in the Anterior Segment and Vascular System of the Eye in Myopic Children After Orthokeratology - Chen, Yanwei; Shen, Xi (Frontiers in Pediatrics, 2021)
Purpose: To analyze changes in the anterior segment, retinal vessel density, and choroidal thickness after orthokeratology (Ortho-K). Methods: Myopic children were enrolled from Ruijin Hospital, Shanghai, China. ORTHO-K lenses and single-vision spectacles were fitted for myopia correction. Ocular measurements were taken at baseline and six months, including axial length (AL), central corneal thickness (CCT), anterior chamber depth (ACD), lens thickness (LT), white to white (WTW), choroidal thickness (ChT), macular vessel density (MVD), and optic disc vessel density (OVD). Results: Seventy-six patients were enrolled in this study, including 40 in the ORTHO-K group and 36 in the control group. At baseline, no parameters between the two groups were statistically different. After six months, changes in CCT and ACD decreased in the Ortho-K group compared with those in the control group (p<0.05); LT and ChT in the Ortho-K group were thicker than those in the control group (p<0.05), while there was no difference in MVD and OVD compared to those in the control group (p>0.05). There were moderate positive correlations between ChT and LT and between ChT and OVD in the Ortho-K group (p<0.05). Conclusion: The changes in the anterior and posterior segments of the eye after Ortho-K lens wearing suggest that the human eye have a powerful compensatory effect on the imposed defocus.